Sugarcane Bagasse-Derived Cellulose Nanocrystal/Polyvinyl Alcohol/Gum Tragacanth Composite Film Incorporated with Betel Leaf Extract as a Versatile Biomaterial for Wound Dressing - Diem, Luong Ngoc; Torgbo, Selorm; Banerjee, Indranil; Pal, Kunal; Sukatta, Udomlak; Rugthaworn, Prapassorn; Sukyai, Prakit (International Journal of Biomaterials, 2023)
In this study, nanocomposite film was fabricated using cellulose nanocrystals (CNCs) as nanofiller in a polymer matrix of polyvinyl alcohol (PVA) and gum tragacanth (GT) via solution casting. CNCs were extracted from sugarcane bagasse using a steam explosion technique followed by acid hydrolysis. Initial analysis of CNCs by transmission electron microscopy (TEM) showed nanosized particles of 104 nm in length and 7 nm in width. Physical and chemical characteristics of neat PVA, PVA/GT, and PVA/GT/CNC films with varying concentrations of CNCs (from 2% to 10%) were analyzed by the scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectrometry, mechanical test, and swelling test. The SEM analysis showed cluster formation of CNCs in the polymer matrix at high concentration. The developed films were transparent. FTIR spectrometry analysis confirmed the chemical functional groups of the various components in the film. The presence of GT and CNCs in the polymer matrix improved the characteristics of films as evident in the prolonged stability for 7 days and increased mechanical properties. The highest elastic modulus of 1526.11 ± 31.86 MPa and tensile strength of 80.39 MPa were recorded in PVA/GT/CNC2 film. The swelling ability, however, decreased from 260% to 230%. Cytotoxicity analysis of the PVA/GT/CNC film showed that it is nontoxic to mouse fibroblast cells L929 with 95% cell viability. Films loaded with betel leaf extract exhibited excellent antibacterial activities against Staphylococcus aureus DMST 8840 and Pseudomonas aeruginosa TISTR 781 with 28.20 ± 0.84 mm and 23.60 ± 0.55 mm inhibition zones, respectively. These results demonstrate that PVA/GT/CNC loaded with the betel leaf extract could act as promising and versatile wound dressings to protect the wound surface from infection and dehydration.